Irreversible Adsorption of Serum Proteins onto Nanoparticles. (17th November 2020) - von Baeckmann, Cornelia; Kählig, Hanspeter; Lindén, Mika; Kleitz, Freddy
Abstract: When a material comes in contact with serum or plasma, proteins will immediately adsorb to its surface. The extent of serum protein adsorption as well as the composition of the protein corona is thought to be decisive for the biological fate. The understanding of the mechanism underlying the concurrent adsorption of multiple proteins and the exact ways by which the adsorbed proteins interact with the biological setting, is still rudimentary. For both cases, a correct estimate of the composition of the protein corona is the key for an improved understanding. The protein corona composition is typically analyzed indirectly through analysis of the supernatant after protein desorption. However, in most cases the particles are not analyzed afterward in order to ensure that all proteins indeed have desorbed. Here, the results related to the analysis of the amounts of proteins in the corona are reported, focusing on the desorbed as well as the fraction of proteins that do not desorb. Irreversible protein adsorption can be observed in some cases. The results show that, in addition of the analysis of the supernatant, analysis of the particles is of critical importance to fully characterize the protein corona formed on nanoparticles. Abstract : The importance of the detailed characterization of the serum protein corona formed around nanoparticles is highlighted, with special emphasis on the protein adsorption/desorption dynamics. Irreversible protein adsorption is observed in some cases, underlining the need to carefully analyze not only desorbed proteins but also serum proteins potentially remaining strongly bonded on the nanoparticles.